Institutional arrangements for implementing One Health and Eco-health - Grace, Delia; Kabayo, W.; McDermott, John J. (2011)
Unprecedented changes to ecosystems and agriculture are resulting in complex health challenges (human, animal and ecosystem) requiring innovative and systemic solutions, such as ecohealth and one health. A central concept of one health and ecohealth is inter-sectoral work between agriculture, health, environmental and other sectors. Understanding the priorities, types of institutional arrangements and mechanisms for working is still evolving and can vary greatly depending on local context and the type of inter-sectoral engagement. Case studies for developing countries in Latin America, Africa and Asia are reviewed, across the spectrum of cross-sectoral integration. Options for institutional arrangements have included joint task forces around specific emergencies, the establishment of joint offices for specific diseases, shared labs and other infrastructure, joint research, integrated disease surveillance, inter-sectoral programs such as veterinary units in public health departments and delivery of services through one health practitioners. From these we present a framework on assessing the efficiency, effectiveness and feasibility of different types of institutional arrangements and for better understanding the barriers and bridges to working across sectors in different countries. This includes criteria for assessing impacts within and between sectors. Lessons learned for prioritizing and implemented joint actions are summarized.